The Role of Clitoral Anatomy in Female to Male Sex Reassignment Surgery. (10th April 2014) - Vukadinovic, Vojkan; Stojanovic, Borko; Majstorovic, Marko; Milosevic, Aleksandar
Abstract : Introduction . Controversies on clitoral anatomy and its role in female sexual function still make clitoral reconstructive surgery very challenging. We evaluated the role of clitoral anatomic features in female to male sex reassignment surgery. Material and Methods . The study included 97 female transsexuals, aged from 18 to 41 years, who underwent single stage metoidioplasty between March 2008 and January 2013. The operative technique involved vaginectomy, the release of clitoral ligaments and urethral plate, urethroplasty by combining buccal mucosa graft and genital flaps, and scrotoplasty with insertion of testicle prostheses. Postoperative questionnaire was used to evaluate aesthetic, functional, and sexual outcome. Results . The mean followup was 30 months. The mean length of the neophallus was 7 cm, compared to mean preoperative length of the hypertrophied clitoris of 3.3 cm. Complications occurred in 27.84% of all patients, related mostly to urethroplasty. Voiding while standing was achieved in all cases. None of the patients had problems in sexual arousal, masturbation, or orgasms. Conclusion . Accurate knowledge of the clitoral anatomy, physiology, and neurovascular supply is crucial for a successful outcome of female to male sex reassignment surgery. Our approach appears to ensure overall satisfaction and high quality of sexual life.